Implementation of Public Health England infection prevention and control guidance in maternity units in response to the COVID-19 pandemic. (November 2022) - Hanley, S.J.; Jones, A.B.; Oberman, J.; Baxter, E.; Sharkey, D.; Gray, J.; Walker, K.F.
Summary: Background: This study aimed to explore the successes and barriers to the implementation of Public Health England (PHE) infection prevention and control guidance in English maternity units during the COVID-19 pandemic. Methods: Qualitative semi-structured interviews with obstetricians, midwives and neonatologists who worked in a maternity unit in England, UK, between March 2020 and July 2021. A thematic analysis was performed. Results: Successes to the implementation of PHE guidance were related to existing infrastructure, training satisfaction, and organisational culture where subthemes considered the importance of a multidisciplinary approach, COVID-19 dedicated roles and hospital-wide communication. Barriers to implementation related to the applicability of the guidance with subthemes highlighting contradictions between updates, specialties and hospitals, undesirable timings and frequency of guidance updates, reductions in staff compliance and delayed implementation. Finally, the layout of some units made it difficult to implement various aspects of the guidance (e.g., social distancing), and many detailed issues related to information technology compatibility, a lack of availability and accessibility to appropriate personal protective equipment (PPE), and variations in testing arrangements between units. Conclusions: This research provides information on the experiences of healthcare professionals working on maternity units during the COVID-19 pandemic. Findings illustrate the importance of effective hospital-wide communication and the need for consistent, easily understood guidance. These results will be used to inform the content of an expert panel consensus meeting.